Women in Wartime Dress Studies from Picture Post 1938-1945 - Howell, Geraldine (Bloomsbury Academic, 2008)
Picture Post magazine was made famous by its pioneering photojournalism, which vividly captured a panorama of wartime events and the ordinary lives affected. This book is the first to examine this fascinating primary source as a cultural record of women's dress history. Reading the magazine's visual narratives from 1938 to 1945, it weaves together the ways in which design, style and fashion were affected by, and responded to, the state of being at war - and the new gender roles it created for women. From the working class of Whitechapel to the beach sets of the Bahamas, and from well-heeled Mayfair to middle-class New York, Women in Wartime takes a wide-angled lens to the fashions and lifestyles of the women featured in Picture Post. Exploring the nature of femininity and the struggle to be fashionable during the war, the book reveals critical connections between clothing and social culture. Drawing on a unique range of photographs, Women in Wartime presents a living history of how women's clothing choices reflect changing perceptions of gender, body, and class during an era of unprecedented social change.